Inherited cancer predisposing mutations in patients with therapy‐related myeloid neoplasms. (9th November 2022) - Shih, Andrew J.; Jun, Tomi; Skol, Andrew D.; Bao, Riyue; Huang, Lei; Vora, Sapana; McNerney, Megan E.; Hungate, Eric A.; Le Beau, Michelle M.; Larson, Richard A.; Elliott, Aaron; Lu, Hsiao‐Mei; et al.
Summary: Some patients with therapy‐related myeloid neoplasms (t‐MN) may have unsuspected inherited cancer predisposition syndrome (CPS). We propose a set of clinical criteria to identify t‐MN patients with high risk of CPS (HR‐CPS). Among 225 t‐MN patients with an antecedent non‐myeloid malignancy, our clinical criteria identified 52 (23%) HR‐CPS patients. Germline whole‐exome sequencing identified pathogenic or likely pathogenic variants in 10 of 27 HR‐CPS patients compared to 0 of 9 low‐risk CPS patients (37% vs. 0%, p = 0.04). These simple clinical criteria identify t‐MN patients most likely to benefit from genetic testing for inherited CPS.